Pengaruh Kualitas Pelayanan Customer Service Terhadap Loyalitas Nasabah Dalam Perspektif Ekonomi Islam - Lafifah Ulfah Dalimunthe; Andrew Hermawan Harahap; Enika Diana Batubara; Riski Fadhil (Jurnal Ilmiah Wahana Pendidikan, 2023)
Customer service is the most important part in a company and can be said to be the spearhead for a company, especially in the banking sector which emphasizes Islamic economic values. Due to increasing banking competition, it is demanded that they must be active in increasing their business both to get new customers and to retain old customers. In an Islamic economic perspective, it also implements a service system that is good, honest, and profitable and not detrimental to both parties, both the company (the person offering the product) and the customer (the person buying it) so that this principle of Islamic economics makes customers loyal to something. company for the products offered. Therefore service is very important, especially customer service because it affects the overall quality of a company in satisfying stated or implied needs.